2018
DOI: 10.1177/1470785318805305
|View full text |Cite
|
Sign up to set email alerts
|

Controlling social desirability bias

Abstract: Social desirability bias can change the results from marketing experiments and surveys. However, there are few illustrations that show how serious social desirability bias can be. This research starts by reviewing the options for identifying and reducing social desirability bias in experiments and surveys and for controlling its effects. Then two examples that use a social desirability bias scale or a transformation of it (that may improve its utility) as control variables are described. Data from a national p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
185
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 384 publications
(235 citation statements)
references
References 101 publications
2
185
0
3
Order By: Relevance
“…Like any other survey, questions related to environmental awareness and SRAS indices are likely affected by the social desirability bias. However, it is suggested that anonymous, self-administered surveys contain fewer desirability biases than telephone and face-to-face surveys [41]. Hence, as the current study conducted a self-administered online survey, I believe such social desirability bias was controlled to a minimum compared to telephone and face-to-face surveys.…”
Section: The Surveymentioning
confidence: 83%
“…Like any other survey, questions related to environmental awareness and SRAS indices are likely affected by the social desirability bias. However, it is suggested that anonymous, self-administered surveys contain fewer desirability biases than telephone and face-to-face surveys [41]. Hence, as the current study conducted a self-administered online survey, I believe such social desirability bias was controlled to a minimum compared to telephone and face-to-face surveys.…”
Section: The Surveymentioning
confidence: 83%
“…While the effect of this bias could not be eliminated completely, maintaining respondent anonymity would mitigate it. 28 In this study, we used anonymized questionnaires. Online submissions could not be traced back to the sender, and paper submissions were through a third party (PSMO secretariat).…”
Section: Discussionmentioning
confidence: 99%
“…The averages were 6.65 in the January 2015 sample and 6.80 in the October sample. Instead of using the sums, a logit transformation was applied to create a measure with a range from 0 to 1 for each respondent, eliminating the measure’s linearity and increasing its slope for biased response totals that were relatively high (Larson, 2019).…”
Section: Methodsmentioning
confidence: 99%